Cell death and iron deposition in the liver in two murine models of acute radiation syndrome - Dmitry T. Bradfield; John E. Slaven; W. Bradley Rittase; Milan Rusnak; Aviva J. Symes; Grace V. Brehm; Jeannie M. Muir; Sang-Ho Lee; Joseph A. Anderson; Regina M. Day (PLoS ONE, 2025)
Different tissues exhibit differential sensitivity to ionizing radiation exposure and display different time courses of pathologies that are not well understood. Ionizing radiation causes hemolysis of red blood cells, causing the release of iron that is taken up by a variety of tissues. The increased iron has been associated with altered expression of iron binding proteins and, in some cases, markers of ferroptosis. Here we examined the time course of iron uptake in murine liver following 60Co total body irradiation (TBI) at 7.9 Gy (LD90/30) and 6.85 Gy (LD0/30). 7.9 Gy induced hydropic degeneration, micro-vesicular steatosis, and inflammatory cell infiltration, whereas at 6.85 Gy the livers displayed only inflammatory cell infiltration. In both cases, iron levels increased significantly, maximal at ~21 days post-TBI. Increased iron was associated with altered expression of ferritin, heme oxygenase, an enzyme required for iron recycling, and the pro-inflammatory cytokine serum amyloid A, maximal ~16–21 days. 7.9 Gy induced liver caspase-3 activation consistent with apoptosis. In contrast, 6.85 Gy induced markers of ferroptosis but not of apoptosis. Our data indicate that iron is deposited in the liver at a delayed time point following radiation and is associated with increased ferritin, HO-1, and inflammatory cytokine production.